Will Folksonomy replace traditional classification of information on the web? a critical study - Wijetunge, Pradeepa (Sri Lanka Library Association, 2010)
There are numerous methods used to organize the contemporary printed literature as well as web-based information. These methods can be categorized as traditional and less-traditional methods. There are many instances in which traditional methods have been adopted to organize web resources, nevertheless it is believed that they were not exploited to the maximum for organizing the web. The second approach to organize information on web is the non-traditional approach of developing new initiatives and innovation which include semantic networks and ontologies and the common term used for all these methods is “Knowledge Organisation Systems”. This second approach is more familiar to the information scientists and computer specialist but unfamiliar to librarians. However even the KOSs were not the ultimate solution for web-organising. They are imprecise because they cannot be easily adopted for the rapid pace of content development brought-about by Web publishing. This sluggishness of the KOSs paved way for another alternative classification - the users to create metadata for the web-based information resources. It is a distributed classification scheme created by a group of individuals, typically the resource users and known as folksonomy. This paper traces the development of folksonomy, its advantages and disadvantages and attempts to answer the question whether traditional classification systems will be replaced by folksonomy.